2012
DOI: 10.1128/aac.01198-12
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacokinetics of Intravaginal Rings Delivering Tenofovir in Pig-Tailed Macaques

Abstract: Antiretroviral-based microbicides applied topically to the vagina may play an important role in protecting women from HIV infection. Incorporation of the nucleoside reverse transcriptase inhibitor tenofovir (TFV) into intravaginal rings (IVRs) for sustained mucosal delivery may lead to increased microbicide product adherence and efficacy compared with those of conventional vaginal formulations. Formulations of a novel "pod IVR" platform spanning a range of IVR drug loadings and daily release rates of TFV were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 45 publications
(85 reference statements)
3
59
1
Order By: Relevance
“…Proinflammatory cytokine levels in the CVL fluid samples as a function of time during PK1 and PK2 did not show statistically significant changes as a result of IVR use except for IL-18 levels in the PK1 low-releasing group, which decreased from those at the baseline upon ring insertion. These results indicate that neither the pod-IVR nor the VRC01-N itself leads to an increased inflammatory response, as has been observed previously for pod-IVRs delivering antiretrovirals (ARVs) in pig-tailed macaques (48,55).…”
Section: Discussionsupporting
confidence: 61%
“…Proinflammatory cytokine levels in the CVL fluid samples as a function of time during PK1 and PK2 did not show statistically significant changes as a result of IVR use except for IL-18 levels in the PK1 low-releasing group, which decreased from those at the baseline upon ring insertion. These results indicate that neither the pod-IVR nor the VRC01-N itself leads to an increased inflammatory response, as has been observed previously for pod-IVRs delivering antiretrovirals (ARVs) in pig-tailed macaques (48,55).…”
Section: Discussionsupporting
confidence: 61%
“…The study timeline and biological sample collection points are shown in Fig. 2 and employed published protocols (15,24). Briefly, six sexually mature female pig-tailed macaques (Macaca nemestrina) were used; three received TDF-FTC IVRs (Table 1), and three received TDF-FTC-MVC IVRs.…”
Section: Materials Tenofovir Disoproxil Fumarate (Tdf) and Emtricitamentioning
confidence: 99%
“…Macaquesized (21) polydimethylsiloxane (PDMS) (silicone) pod-IVRs were prepared in a multistep process that has been described in detail elsewhere (13,15). Six pods per combination IVR were used in two different formulations, i.e., one containing three pods each of TDF and FTC and another containing two pods each of TDF, FTC, and MVC (Table 1 and Fig.…”
Section: Materials Tenofovir Disoproxil Fumarate (Tdf) and Emtricitamentioning
confidence: 99%
See 2 more Smart Citations